Kuwaiti - British relations since the beginning of the 19th century tillAL-Himaya treaty 1899 - Alaa Eddin, Ibrahim; ayzouki , Rami (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The Arabian Gulf region, including Kuwait, was part of the Ottoman Empire, enjoying an almost autonomous role in managing its affairs. Given the Persian Gulf, India became the scene of a conflict between the European states and the Ottoman Empire. And the fact that the Arabian Gulf was subject to nominal Ottoman state, which left the matter of internal affairs of its local rulers and the weakness of central government, and the lack of interest in it only after the opening of the Suez Canal in 1869 on the one hand, and the disintegration of his emirates and manshes and the lack of coordination and unity among them from the othe, It led to the success of Britain to impose its control over the Arabian Gulf in accordance with a series of agreements with the princes and rulers of those regions,And entered into a clearly defined political conflict with the Ottoman Sultanate to control and impose protection on Kuwait. This conflict emerged when Sheikh Mubarak bin Sabah al-Sabah came to power in 1896-1916, and he became a haven for all the opponents of the Ottoman Empire. Has to face in front of them only the alliance with Britain, which took advantage of that period to strengthen its influence in the Arabian Gulf. If Britain was not able to put Kuwait under its protection in the first stage, maintaining the independence of the Presbyterian from the Ottoman Empire was in its interest.